OP35 Natural history of anal ulcerations in pediatric-onset Crohn's Disease: A population-based study. (21st January 2022) - Mortreux, P; Leroyer, A; Dupont, C; Ley, D; Bertrand, V; Spyckerelle, C; Guillon, N; Desreumaux, P; Gower-Rousseau, C; Savoye, G; Fumery, M; Turck, D; et al.
Abstract: Background: Anal ulcerations are frequently observed in Crohn's disease (CD). Their natural history remains poorly known, especially in pediatric-onset CD. The aims of this study were: to determine in a population-based study the risk of anal ulcerations in pediatric onset CD; to identify risk factors for anal ulcerations; to evaluate the risk of progression towards suppurative lesions; to evaluate the risk factors of progression towards suppurative lesions. Methods: All patients with a diagnosis of CD before the age of 17 years between 1988 and 2011 within the population-based registry EPIMAD were followed retrospectively until 2013. A specific collection of additional data was performed in patients with anal ulcerations at diagnosis or during follow-up. The variables collected included: proctological examination, diagnostic management (perineal MRI, endoscopic ultrasound, examination under general anaesthesia) and treatment (medical or surgical). Multivariate Cox models were used to identify factors associated with anal ulcerations and factors of progression towards suppurative lesions. An adjusted time-dependent Cox model was used to evaluate the risk of progression of anal ulcerations towards suppurative lesions. Results: 1005 patients were included (females, 450 (44.8%); median age at diagnosis 14.4 years (IQR, 12.0–16.1)). 257 (25.6%) had anal ulceration at diagnosis. Cumulative incidence of anal ulceration at 5 and 10 years from diagnosis was 38.4% (CI95%, 35.2–41.4) and 44.0% (CI95%, 40.5–47.2). The presence of extra-intestinal manifestations (HR 1.46, CI95% 1.19–1.80, p=0.0003) and upper digestive location (HR 1.51, CI95% 1.23–1.86, p<0.0001) at diagnosis were associated with the occurrence of anal ulceration. Conversely, ileal location at diagnosis was associated with a lower risk of anal ulceration (L2 vs L1 HR 1.51, CI95% 1.11–2.06, p=0.0087; L3 vs L1 HR 1.42, CI95% 1.08–1.85, p=0.0116). Among the 352 patients with at least one episode of anal ulceration, 82 (23.3%) developed perianal suppuration after a median follow-up of 5.7 years (IQR, 2.8–10.6). The risk of perianal suppuration was doubled in patients with anal ulceration compared to those who did not have any ulceration (HR 2.0, CI95% 1.45–2.74, p<0.0001). In patients with anal ulceration, the diagnostic period (before or since the "biologic era"), exposure to immunosuppressants and/or anti-TNF did not influence the risk of perianal suppuration. Conclusion: Anal ulceration is frequent in pediatric-onset CD, with nearly half of patients presenting with at least one episode after 10 years of evolution. Perianal suppurations are twice as frequent in patients with present or past anal ulceration. These results plead for a proactive therapeutic approach in case of anal ulcerations.